Aristotle’s Resolution of the Aporia about Coming-to-be in Physica I,8 - Rossi, Gabriela (2017)
In Physica I,8 Aristotle endeavors to show that a long-term Eleatic puzzle about coming-to-be can be resolved by appealing to his own ontological principles of change (substratum, privation, and form). In this paper, I posit that the key to Aristotle’s resolution lies in the introduction of aspectual distinctions within numerical unities. These distinctions within the terminus a quo and the terminus ad quem of coming-to-be made it possible for Aristotle to maintain, while answering the puzzle, that there is no coming-to-be ex nihilo and, at the same time, that the product of coming-to-be is something that did not exist before; i.e. that there is coming-to-be. Finally, I suggest that this resolution could be seen as an interesting case of the application of conceptual tools developed in the Sophistici Elenchi, and I analyze the advantages of this resolution over the Platonic resolution of a similar sort of Eleatic problem.